Anaphylactic shock during cement implantation of a total hip arthroplasty in a patient with underlying mastocytosis: case report of a rare intraoperative complication. Issue 1 (December 2016) - ten Hagen, Anita; Doldersum, Pieter; van Raaij, Tom
Abstract Background Cemented total hip arthroplasty (THA) is a safe and common procedure. In rare cases life threatening bone cement implantation syndrome (BCIS) may occur, which is commonly caused by pulmonary embolism (PE). Case presentation We describe the rare case of a 70-year old patient who underwent an elective total hip replacement. Before surgery he was diagnosed with underlying systemic indolent mastocytosis, a rare pathological disorder that may result in anaphylaxis after massive systemic mast cell activation. Triggers may be IgE-mediated, direct mast cell activation, or unclear. Some patients may be at risk for severe non IgE-mediated reactions, such as those experienced with nonsteroidal anti-inflammatory drugs, or with perioperative muscle relaxants. During cementing of the acetabular component, our patient developed acute hypotension (blood pressure dropped from 90/50 to 60/40 mmHg, and saturation dropped from 95 to 80 %). The differential diagnosis of acute PE was excluded (no signs of breathing abnormalities during physical examination, normal arterial blood sample, and no electrocardiography or cardiac ultrasound abnormalities). The patient was diagnosed with acute anaphylactic shock, which was successfully managed by 100 % oxygen administration, rapid fluid induction, and vasoconstrictive drug therapy. He recovered hemodynamically within 15 min, did not lose consciousness, and did not develop angioedema or an urticarial rash. Forty-five minutes after onset of the symptoms, the surgical procedure was completed after inserting a press fitted uncemented femoral stem component. The patient was transported to the Intensive Care Unit (ICU) for optimal monitoring. Our patient had an uneventful recovery. Within six hours after surgery he started to ambulate following our standard fast-track rehabilitation regime. Post-operative day one he was discharged to the specialized Orthopedic Department, and after five hospital days discharged to his home. Twelve months after THA surgery our patient was satisfied with an optimal functional status of his hip joint replacement. Conclusion The differential diagnosis of anaphylactic shock must be taken into consideration in patients with acute hypotension during cementing of total hip arthroplasty components. Patients with underlying mastocytosis are at particular risk of this potential life-threatening intra-operative complication. This rare entity should be taken into consideration during the pre-operative risk stratification and shared decision-making process for elective cemented joint replacement.